MODEL PREDIKSI FINANCIAL DISTRESS PERUSAHAAN PERDAGANGAN ECERAN: PENDEKATAN ALTMAN Z-SCORE - Zannati, Rachma; Dewi, Evita Rosdiana (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to prove the financial distress prediction model through the Z-Score (Altman) approach to financial performance. The number of samples is 21 retail trading companies listed on the Stock Exchange for five years with a purposive sampling technique. Research findings prove that financial performance can predict Financial Distress in the retail trade sector through Working Capital to Total Assets, Debt to Asset Ratio, and Return on Asset variables. The results of research for investors become one of the basic considerations for determining future stock investment decisions. In addition, the results of the study can provide an evaluation of the company's performance in maintaining the stability of business continuity in order to avoid financial distress. Keywords: Altman Z-Score, Financial Performance